The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini) - Cavichioli1, Rodney R.; Mejdalani, Gabriel (Zootaxa, 2017)
A new species of the Neotropical sharpshooter genus Iragua Melichar, 1926, I. albinoi sp. nov., is described and illustrated from the Colombian department of Huila (holotype deposited in Coleção Entomológica Pe. Jesus S. Moure, Departamento de Zoologia, Setor de Ciências Biológicas, Universidade Federal do Paraná). The new taxon can be readily distinguished from the other 13 known species of the genus by the presence of a pair of unciform processes at the aedeagal atrium, as well as by the color pattern of the forewings. The first detailed description of the female terminalia of a species of Iragua (I. ferruginea Cavichioli, 1991 from the Brazilian state of Rondônia) and an updated key to males of the genus are also provided.